Development of Student Government E-Voting Application - Tabanao, Eden Grace; Cece, Jed Christian (Journal of Interdisciplinary Perspectives, 2025)
This study underscores the transformative potential of an e-voting mobile application in enhancing the election process at NORSU-Guihulngan Campus by improving efficiency, reliability, and transparency. This innovative solution ensures a streamlined, fair, and secure electoral process by addressing the limitations of traditional manual voting systems. The descriptive-developmental method employed included planning, prototyping, testing, and data gathering. A survey was distributed to 106 respondents, including students and IT experts, to evaluate the manual voting system and assess the e-voting application’s functionality. Pilot tests were conducted with criteria focusing on user interface, security, accessibility, transparency, and reliability, supported by statistical analysis. The e-voting application exhibited exceptional performance across all evaluated aspects. The user interface and security scored an average of 4.39, reflecting excellent design and robust data protection. Accessibility achieved the highest rating at 4.46, ensuring seamless usability for diverse users. Transparency and reliability were rated at 4.31 and 4.41, respectively, underscoring the system’s openness and consistent functionality. Overall, the application achieved a total average rating of 4.39, confirming its effectiveness as a voting solution. The application’s usefulness was evaluated across six key features: accessibility, time and cost efficiency, real-time results, enhanced accuracy, increased security, and audit trail transparency. Accessibility and real-time results received scores of 3.50, while time and cost efficiency achieved 3.60. Enhanced accuracy and security also scored 3.50, minimizing errors and fostering trust. Audit trail transparency, rated at 3.40, emphasized the system’s accountability. These findings validate the application’s ability to revolutionize student elections at NORSU-Guihulngan and provide a scalable model for similar institutional contexts. The study highlights the importance of integrating modern technology into election systems, paving the way for broader adoption in academic and institutional settings to ensure reliable and transparent processes.